STUDENTS’ PERFORMANCE SKILLS IN CREATIVE MATHEMATICAL REASONING - Heris Hendriana; Rully Charitas Indra Prahmana; Wahyu Hidayat (IKIP Siliwangi and I-MES, 2018)
This study aims to examine mathematics teacher-candidate students’ mathematical creative reasoning ability based on the level of Adversity Quotient (AQ). This study uses a mixed method of sequential type by combining quantitative and qualitative methods in order. Population in this study is all students attending the course of Calculus in Mathematics Education of Master Program at STKIP Siliwangi that consist of 270 students divided into six classes. The results are AQ gives effect to the achievement of students’ mathematical creative reasoning abilities based on the whole and the type of AQ climber, champer, and quitter. The achievement of students’ mathematical creative reasoning abilities and based on AQ, the champer and climber fall into the medium category, while on the quitter type, it falls into the category of low. On the other hands, the achievement of students’ mathematical creative reasoning abilities is yet to be achieved well at the indicator of novelty.